A high-strength gradient structure FeCoNiCr series high-entropy alloy and preparation method thereof
By performing multiple steps such as arc smelting and heat treatment on FeCoNiCr-based high-entropy alloys, high-strength high-entropy alloys with gradient nanostructures were prepared, which solved the problem of taking into account both strength and plasticity of the existing high-entropy alloys, and significantly improved its mechanical properties and surface properties.
Patent Information
- Application Number
- CN202310218969.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-09
AI Technical Summary
While increasing strength, existing high-entropy alloys reduce plasticity, and ignore the performance of the material surface, and have limited applications in aerospace and other fields.
By arc smelting, heat treatment, cold rolling, solid solution treatment, aging treatment and ultrasonic surface nanomodification treatment on the FeCoNiCr-based high-entropy alloy raw materials, a (FeCoNiCr)92Ti3.5Al4.5 high-entropy alloy was prepared to form a gradient nanostructure.
On the premise of ensuring good plasticity, the strength and surface properties of high-entropy alloys are improved, with a yield strength exceeding 1200MPa, a tensile strength exceeding 1550MPa, and an elongation exceeding 12%, expanding its application in aerospace and other fields.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a FeCoNiCr series high entropy alloy and a preparation method thereof, in particular to a FeCoNiCr series high entropy alloy with high strength, high plasticity and gradient nanostructure and a preparation method thereof, belonging to the technical field of preparation and processing of new alloy materials. Background Art
[0002] With the continuous development of social science and technology, the performance of traditional alloy materials (strength and plasticity at room temperature, etc.) cannot meet the needs of industrial manufacturing, such as the aerospace field. Compared with traditional alloys, high entropy alloys are composed of multiple main elements with equal or nearly equal atomic ratios and have a larger mixed entropy. In addition, high entropy alloys have four major effects, which are high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect in thermodynamics, structure, dynamics and performance. High entropy alloys have excellent properties such as high temperature resistance and high wear resistance, but their low strength limits the application and development of high entropy alloys.
[0003] At room temperature, most existing high entropy alloys are strengthened through a series of processes such as alloying and thermomechanical treatment. However, traditional treatment methods will reduce plasticity while increasing strength, and also ignore the importance of material surface performance in practical engineering applications in aerospace and other fields. Since most material failures (fatigue, wear, corrosion) are closely related to the performance of the material surface, such as aircraft will repeatedly suffer from unstable airflow, turbulence and other conditions during long-term service, parts will deform during extrusion or microcracks will appear on the surface, which is an important test for the surface performance of the material.
[0004] Therefore, it is urgent to prepare a high-strength FeCoNiCr high-entropy alloy to improve its mechanical properties while ensuring good plasticity, improve the performance of the alloy surface, and expand the application field of high-entropy alloys. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a high-strength gradient structure FeCoNiCr series high entropy alloy and a preparation method thereof, wherein the alloy raw materials are subjected to arc melting, heat treatment, cold rolling, solution treatment, aging treatment and ultrasonic surface nano-modification treatment in sequence to obtain (FeCoNiCr) 92 Ti 3.5 Al 4.5 At room temperature, the high entropy alloy can have good strength and a gradient hardened layer on the alloy surface while ensuring good plasticity.
[0006] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a high-strength gradient structure FeCoNiCr series high entropy alloy, comprising the following steps:
[0007] S1. Prepare metal raw materials Fe, Co, Ni, Cr, Ti, and Al in a weight ratio of 23:23:23:23:3.5:4.5 in molar ratio;
[0008] S2. Put the above metal raw materials into a vacuum arc furnace, and then evacuate the vacuum arc furnace to 8×10 -3 Pa, then argon gas is introduced into the vacuum arc furnace to perform arc melting on the metal raw materials at a melting temperature of 1200-1600°C, and the melting is repeated 5-7 times to make the components in the raw materials evenly mixed. After the melting is completed, it is cooled to room temperature to obtain a high entropy alloy cast state;
[0009] S3, sequentially subjecting the arc-melted high entropy alloy casting to heat treatment, cold rolling, solution treatment, aging treatment and ultrasonic surface nano-modification treatment, and cooling to room temperature after all treatments to obtain a high-strength gradient structure FeCoNiCr high entropy alloy;
[0010] During the heat treatment, the temperature is raised to 1000-1200°C at a rate of 20°C / min, and then kept at this temperature for 4-6 hours;
[0011] During the cold rolling process, at room temperature, the alloy is first cold rolled with a deformation amount of 2% each time until the alloy deformation amount is 60%, and then with a deformation amount of 1% each time to finally reach an alloy deformation amount of 70%~80%;
[0012] During the solution treatment, the temperature was raised to 850-950°C at a rate of 20°C / min and then kept at this temperature for 0.5h;
[0013] During the aging treatment, the temperature is raised to 620-680°C at a rate of 20°C / min and then kept at this temperature for 28-32h;
[0014] In the ultrasonic surface nano-modification treatment, ultrasonic nano-surface modification equipment is used to process the alloy surface at an ultrasonic frequency of 28~30kHz, the tool head pressure is 150~300N, and the rolling times are 4~8 times.
[0015] In step S1, the raw materials of Fe, Co, Ni, Cr, Ti and Al are all metal blocks with a purity greater than 99.9%.
[0016] In the step S2, preferably, the smelting temperature is 1400° C., and the smelting is repeated 5 times.
[0017] In the step S2, preferably, the temperature is raised to 1200°C at a heating rate of 20°C / min during the heat treatment, and then kept at this temperature for 6 hours.
[0018] In the step S3, preferably, during the cold rolling process at room temperature, the alloy is first cold rolled with a deformation amount of 2% each time until the alloy deformation amount is 60%, and then with a deformation amount of 1% each time to finally reach an alloy deformation amount of 75%.
[0019] In the step S3, preferably, the temperature is raised to 900°C at a heating rate of 20°C / min during the solution treatment, and then kept at this temperature for 0.5h.
[0020] In the step S3, preferably, the temperature is raised to 650°C at a heating rate of 20°C / min during the aging treatment, and then kept at this temperature for 30 hours.
[0021] In the step S3, preferably, the ultrasonic frequency is 28 kHz, the pressure is 300 N, and the number of rolling passes is 8.
[0022] A high-strength gradient structure FeCoNiCr high-entropy alloy prepared by the above preparation method, wherein the atomic percentage composition of the high-strength gradient structure FeCoNiCr high-entropy alloy is (FeCoNiCr) 92 Ti 3.5 Al 4.5 .
[0023] The (FeCoNiCr) 92 Ti 3.5 Al 4.5 The surface of the material is a gradient nanostructure, with a yield strength of more than 1200MPa and a tensile strength of more than 1550MPa.
[0024] The beneficial effects of the present invention are:
[0025] 1) The present invention obtains (FeCoNiCr) by sequentially subjecting the alloy raw materials to arc melting, heat treatment, cold rolling, solution treatment, aging treatment and ultrasonic surface nano-modification treatment. 92 Ti 3.5 Al 4.5 At room temperature, the high entropy alloy can have good strength and a gradient hardened layer on the alloy surface while ensuring good plasticity.
[0026] 2) The present invention prepares a high entropy alloy with a yield strength of more than 1200MPa, a tensile strength of more than 1550MPa, and an elongation after fracture of more than 12%. While ensuring good plasticity, the strength is greatly improved, thereby expanding the application of high entropy alloys in the fields of aerospace and aviation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a stress-strain curve diagram of the high entropy alloy prepared in Example 1 of the present invention;
[0028] Figure 2 This is a stress-strain curve diagram of the high entropy alloy prepared in Example 2 of the present invention;
[0029] Figure 3 This is a stress-strain curve diagram of the high entropy alloy prepared in Example 3 of the present invention;
[0030] Figure 4 This is a microstructure diagram of a high entropy alloy prepared in Example 3 of the present invention;
[0031] Figure 5 A stress-strain curve diagram of a high entropy alloy prepared in Comparative Example 1 of the present invention;
[0032] Figure 6 A stress-strain curve diagram of a high entropy alloy prepared in Comparative Example 2 of the present invention;
[0033] Figure 7 This is a stress-strain curve of the high entropy alloy prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments.
[0035] The metal elements Fe, Co, Ni, Cr, Ti, and Al used in the following examples are all pure metals with a purity of 99.9 wt.% or more.
[0036] Embodiment 1: A method for preparing a high-strength gradient structure FeCoNiCr-based high-entropy alloy, comprising the following steps:
[0037] S1. Prepare metal raw materials Fe, Co, Ni, Cr, Ti, and Al in a weight ratio of 23:23:23:23:3.5:4.5 in molar ratio;
[0038] S2. Put the above metal raw materials into a vacuum arc furnace, and then evacuate the vacuum arc furnace to 8×10 -3 Pa, then argon gas is introduced into the vacuum arc furnace to perform arc melting on the metal raw materials at a melting temperature of 1400°C, and the melting is repeated 5 times to make the components in the raw materials evenly mixed. After the melting is completed, it is cooled to room temperature to obtain a high entropy alloy cast state;
[0039] S3, sequentially subjecting the cast state of the high entropy alloy after arc melting to heat treatment, cold rolling, solution treatment, aging treatment and ultrasonic surface nano-modification treatment, and cooling to room temperature after all treatments to obtain a FeCoNiCr high entropy alloy finished product 1;
[0040] In the heat treatment, the temperature was raised to 1000℃ at a rate of 20℃ / min, and then kept warm for 4h; in the cold rolling treatment, at room temperature, the alloy was first cold rolled with a deformation amount of 2% each time until the deformation amount of the alloy was 60%, and then the deformation amount of the alloy was finally reached to 70% with a deformation amount of 1% each time; in the solid solution treatment, the temperature was raised to 880℃ at a rate of 20℃ / min, and then kept warm for 0.5h; in the aging treatment, the temperature was raised to 680℃ at a rate of 20℃ / min, and then kept warm for 32h; in the ultrasonic surface nano-modification treatment, the ultrasonic nano-surface modification equipment was used to process the alloy surface at an ultrasonic frequency of 28kHz, with a tool head pressure of 150N, 4 rolling times, a rolling ball diameter of 7mm, a feed amount of 0.05mm, and a vibration amplitude of 10mm.
[0041] The performance of the high entropy alloy product 1 was tested and the following results were obtained: Figure 1 The stress-strain curve shown has a yield strength of 1148 MPa, a tensile strength of 1412 MPa, and an elongation of 13.5%.
[0042] Embodiment 2: The experimental conditions different from those of embodiment 1 are:
[0043] In arc melting, the melting temperature is 1600℃, and the melting is repeated 7 times; in heat treatment, the temperature is increased to 1100℃ at a heating rate of 20℃ / min, and then kept warm for 5h; in cold rolling treatment, at room temperature, the alloy is first cold rolled with a deformation amount of 2% each time until the alloy deformation amount is 60%, and then the alloy deformation amount is finally reached at 1% each time. 75%; in solution treatment, the temperature is increased to 920℃ at a heating rate of 20℃ / min, and then kept warm for 0.5h; in aging treatment, the temperature is increased to 620℃ at a heating rate of 20℃ / min, and then kept warm for 28h; in ultrasonic surface nano-modification treatment, the blade pressure is 200N and the number of rolling passes is 6; after all treatments are completed, it is cooled to room temperature to obtain the FeCoNiCr high entropy alloy product 2.
[0044] The performance of the high entropy alloy product 2 was tested and the following results were obtained: Figure 2 The stress-strain curve shown has a yield strength of 1213 MPa, a tensile strength of 1512 MPa, and an elongation of 13%.
[0045] Embodiment 3: The experimental conditions different from those of embodiment 1 are:
[0046] In arc melting, the melting temperature is 1200℃, and the melting is repeated 6 times; in heat treatment, the temperature is increased to 1200℃ at a heating rate of 20℃ / min, and then kept warm for 6h; in cold rolling treatment, at room temperature, the alloy is first cold rolled with a deformation amount of 2% each time until the alloy deformation amount is 60%, and then the alloy deformation amount is finally reached at 1% each time. 80%; in solution treatment, the temperature is increased to 900℃ at a heating rate of 20℃ / min, and then kept warm for 0.5h; in aging treatment, the temperature is increased to 650℃ at a heating rate of 20℃ / min, and then kept warm for 30h; in ultrasonic surface nano-modification treatment, the blade pressure is 300N and the number of rolling passes is 8; after all treatments are completed, it is cooled to room temperature to obtain the FeCoNiCr high entropy alloy product 3.
[0047] The performance of the high entropy alloy product 3 was tested and the following results were obtained: Figure 3 The stress-strain curve shown in the figure shows that the yield strength is 1282MPa, the tensile strength is 1558MPa, and the elongation is 12%. The microstructure of the high entropy alloy product 3 was measured by scanning electron microscopy EBSD, as shown in the figure below: Figure 4 As shown, the average grain size of the alloy surface can reach 0.81μm, and the refinement depth is about 195μm.
[0048] Comparative Example 1: Referring to the experimental conditions of the above-mentioned Example 1, only the alloy material is subjected to arc melting treatment to obtain a FeCoNiCr-based high-entropy alloy reference product 1.
[0049] The performance of the high entropy alloy reference product 1 was tested and the following results were obtained: Figure 5 The stress-strain curve shown in the figure shows that the yield strength is 306 MPa, the tensile strength is 592 MPa, and the elongation is 24.5%.
[0050] Control Example 2: Referring to the experimental conditions of Example 2 above, only the alloy material is subjected to arc melting, heat treatment and cold rolling in sequence to obtain FeCoNiCr high entropy alloy reference product 2.
[0051] The performance of high entropy alloy reference product 2 was tested and the results were as follows: Figure 6 The stress-strain curve shown has a yield strength of 1363 MPa, a tensile strength of 1440 MPa, and an elongation of 2.3%.
[0052] Control Example 3: Referring to the experimental conditions of Example 3 above, in addition to the ultrasonic surface nano-modification treatment, the alloy material is subjected to other treatments to obtain FeCoNiCr-based high entropy alloy reference product 3.
[0053] The performance of the high entropy alloy reference product 3 was tested and the following results were obtained: Figure 7 The stress-strain curve shown has a yield strength of 1002MPa, a tensile strength of 1358MPa, and an elongation of 23%.
[0054] Combination Figures 1 to 3 It can be seen from the experimental results that by changing the experimental conditions in Examples 1 to 3, the yield strength and tensile strength are improved, and the elongation is reduced. This reflects that when the static pressure and the number of rolling times increase, the surface strengthening effect is more obvious, but the more serious plastic deformation of the surface causes the elongation to decrease.
[0055] Combination Figures 5 to 7 From the experimental results, it can be seen that by successively increasing the experimental treatment methods in control examples 1 to 3, the yield strength and tensile strength in control example 2 reached the highest, and the elongation was the lowest. This reflects that cold rolling can greatly improve the strength of the alloy, but due to work hardening and other reasons, the plasticity is severely lost, and subsequent treatment is required to reduce the internal residual stress and improve the plasticity of the alloy.
[0056] In addition, Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 2 and Comparative Example 2 are compared with each other. Figures 1 to 7 From the experimental results, it can be seen that the ingot itself has component segregation after smelting. In addition, in order to improve the mechanical properties of the alloy, the strength of the alloy is greatly improved after cold rolling, but the plasticity loss is serious due to work hardening and other reasons.
[0057] The heat treatment method can make the element composition more uniform; the solid solution and aging methods can eliminate the internal stress of the alloy and improve the work hardening, thereby improving the plasticity of the alloy. In the case of good plasticity, ultrasonic surface nano-modification treatment can further improve the strength of the alloy and improve the performance of the alloy surface to form a gradient hardened layer. Therefore, the above processing steps are indispensable and the order of the steps cannot be changed. Compared with the prior art, it can avoid the shortcomings in its processing process, comprehensively improve the mechanical properties of the alloy, and have a gradient nanostructure.
[0058] The present invention prepares a high entropy alloy with a yield strength exceeding 1200 MPa, a tensile strength exceeding 1550 MPa, and an elongation after fracture exceeding 12%. While ensuring good plasticity, the strength is greatly improved, thereby expanding the application of high entropy alloys in the fields of aerospace and aviation.
[0059] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in this field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-strength gradient structure FeCoNiCr high-entropy alloy, characterized in that: The following steps are involved: S1. Prepare metal raw materials Fe, Co, Ni, Cr, Ti, and Al in a weight ratio of 23:23:23:23:3.5:4.5 in molar ratio; S2. Put the above metal raw materials into a vacuum arc furnace, and then evacuate the vacuum arc furnace to 8×10 -3 Pa, then argon gas is introduced into the vacuum arc furnace to perform arc melting on the metal raw materials at a melting temperature of 1200-1600°C, and the melting is repeated 5-7 times to make the components in the raw materials evenly mixed. After the melting is completed, it is cooled to room temperature to obtain a high entropy alloy cast state; S3, sequentially subjecting the arc-melted high entropy alloy casting to heat treatment, cold rolling, solution treatment, aging treatment and ultrasonic surface nano-modification treatment, and cooling to room temperature after all treatments to obtain a high-strength gradient structure FeCoNiCr high entropy alloy; During the heat treatment, the temperature is raised to 1000-1200°C at a rate of 20°C / min, and then kept at this temperature for 4-6 hours; During the cold rolling process, at room temperature, the alloy is first cold rolled with a deformation amount of 2% each time until the alloy deformation amount is 60%, and then with a deformation amount of 1% each time to finally reach an alloy deformation amount of 70%~80%; During the solution treatment, the temperature was raised to 880-920°C at a rate of 20°C / min and then kept at that temperature for 0.5h; During the aging treatment, the temperature is raised to 620-680°C at a rate of 20°C / min and then kept at this temperature for 28-32h; In the ultrasonic surface nano-modification treatment, ultrasonic nano-surface modification equipment is used to process the alloy surface at an ultrasonic frequency of 28~30kHz, the tool head pressure is 150~300N, and the rolling times are 4~8 times.
2. The preparation method according to claim 1, characterized in that: In step S1, the raw materials of Fe, Co, Ni, Cr, Ti and Al are all metal blocks with a purity greater than 99.9%.
3. The preparation method according to claim 1, characterized in that: In the step S2, preferably, the smelting temperature is 1400° C., and the smelting is repeated 5 times.
4. The preparation method according to claim 1, characterized in that: In the step S2, preferably, the temperature is raised to 1200°C at a heating rate of 20°C / min during the heat treatment, and then kept at this temperature for 6 hours.
5. The preparation method according to claim 1, characterized in that: In the step S3, preferably, during the cold rolling process at room temperature, the alloy is first cold rolled with a deformation amount of 2% each time until the alloy deformation amount is 60%, and then with a deformation amount of 1% each time to finally reach an alloy deformation amount of 75%.
6. The preparation method according to claim 1, characterized in that: In the step S3, preferably, the temperature is raised to 900°C at a heating rate of 20°C / min during the solution treatment, and then kept at this temperature for 0.5h.
7. The preparation method according to claim 1, characterized in that: In the step S3, preferably, the temperature is raised to 650°C at a heating rate of 20°C / min during the aging treatment, and then kept at this temperature for 30 hours.
8. The preparation method according to claim 1, characterized in that: In the step S3, preferably, the ultrasonic frequency is 28 kHz, the pressure is 300 N, and the number of rolling passes is 8.
9. A high-strength gradient structure FeCoNiCr-based high-entropy alloy is prepared according to the preparation method according to any one of claims 1 to 8, characterized in that: The atomic percentage composition of the high-strength gradient structure FeCoNiCr high-entropy alloy is (FeCoNiCr) 92 Ti 3.5 Al 4.5 .
10. The high-strength gradient structure FeCoNiCr-based high-entropy alloy according to claim 9, characterized in that: The (FeCoNiCr) 92 Ti 3.5 Al 4.5 The surface of the material is a gradient nanostructure, with a yield strength of more than 1200MPa and a tensile strength of more than 1550MPa.
Citation Information
Patent Citations
High-entropy alloy with dispersion nano-sized precipitate strengthening effect and preparing method thereof
CN104694808A
Method for improving surface performance of single-phase high-entropy alloy
CN109097708A